Variability in different isolates of Penicillium italicum causing blue mould rot in orange (Citrus reticulata) (Current Horticulture, 2024)
Seven isolates of blue mould fungi (Penicillium italicum), causing blue mould rot on orange (Citrus reticulata Blanco) isolated  from Jobner region exhibited variable growth on artificial culture media (PDA). The PI-1 appeared as dark green centre with white  periphery. The other isolates had different colony characters with green to light blue centre surrounded by cottony to profuse colony  peripheries. The disease intensities of blue mould isolates were also variable. The PI-1, PI-2 and PI-3 were at par, while maximum  intensity (57.76 %) was recorded in PI-1 and minimum (21.12 %) in PI-7.
Keywords: Morphological; Pathological; Isolates; Blue mould rot; Cultural variability